Hmotná podstata genetických informací - nukleové kyseliny - Brdička, R (Klinicka onkologie, 2012)
If we look at the history of our knowledge of nucleic acids, we would see in the distant past of 140 years Friedrich Miescher who had identified the acidic substance within the cell nucleus, which he called nuclein. About 70 years after his initial observation, this substance was connected with genetic information. This very substantial finding happened during the World War II. This was the impulse that research of nucleic acids received to speed up continuously growing mountain of information, which is more and more difficult to understand. Another eruption of new information about our genome was the result of ten years of intensive cooperation of many manufacturers divided into two competitive blocks which offered us knowledge of nucleotide sequence of all 46 DNA molecules. The year 2000 became the landmark marking the start of the postgenomic era. It did not mean that human genome was totally explored, but the cornerstone has been settled. Since then, we could concentrate our efforts on variability; use of the project of 1,000 genomes brought many important findings, eg. copy number variability (CNV) exceeds the single nucleotide polymophisms (SNP). Also intergenomic relationships, studies on function and pathways began to be much more understandable by elucidation of the genome primary structure. NGS as a tool also accelerated the epigenetic research. All this improved molecular diagnostics by discovering many new markers playing their role in disease and treatment and allowed us to enter the field of multifactorial illnesses including cancer. The progress in diagnostic technologies which has happened during the last decade forced our research teams to include other professions - eg. bioinformatics.
Keywords: Molecular Diagnostic Techniques; diagnostické techniky molekulární; lidé; dějiny 21. století; dějiny 20. století; nukleové kyseliny; History, 20th Century; History, 21st Century; lékařská genetika; Nucleic Acids; Humans; Genetics, Medical